2018
DOI: 10.1086/697522
|View full text |Cite
|
Sign up to set email alerts
|

Visual Stimuli for the Induction of Hunting Behavior in Cuttlefish Sepia pharaonis

Abstract: Cuttlefish exhibit typical hunting behavior, including elongating tentacles against specific prey such as prawn and mysid shrimp. Cuttlefish hunting behavior involves three different actions: attention, positioning, and seizure. Hunting behavior is innate and stereotypic behavior, and it is present in newly hatched juveniles. Factors associated with prey are known to induce this behavior, similar to the sign stimulus, whereby young herring chicks imitate pecking behavior against a red dot on their parent's bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Cephalopods have complex brains and central nervous systems that provide them with excellent learning and memorization abilities (Cole and Adamo, 2005;Correia et al, 2005;Cartron et al, 2013;Yang and Chiao, 2016;Zepeda et al, 2017;Shinzato et al, 2018;Yasumuro and Ikeda, 2018). As a member of the cephalopod family, the pharaoh cuttlefish has been proven to have number sense and excellent learning ability (Yang and Chiao, 2016;Yasumuro and Ikeda, 2018;Huang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cephalopods have complex brains and central nervous systems that provide them with excellent learning and memorization abilities (Cole and Adamo, 2005;Correia et al, 2005;Cartron et al, 2013;Yang and Chiao, 2016;Zepeda et al, 2017;Shinzato et al, 2018;Yasumuro and Ikeda, 2018). As a member of the cephalopod family, the pharaoh cuttlefish has been proven to have number sense and excellent learning ability (Yang and Chiao, 2016;Yasumuro and Ikeda, 2018;Huang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (1991) used various artificial baits as feed for cultured S. officinalis and reported that artificial pellets had the longest latency-to-grab time, whereas rod-shaped artificial feed (e.g., hot dog-shaped feed) exhibited a shorter latency-to-grab time. Castro et al (1993) and Shinzato et al (2018) reported that cuttlefish were more attracted to shrimp-shaped bait. Thus, artificial feed should be shaped like a rod or a flat rod.…”
Section: Discussionmentioning
confidence: 99%
“…Cues from the prey tube may inhibit striking but could be insufficient to reduce the overall interest in the prey. This is because prey presence is a strong visual stimulus for initiating attention and positioning phases in cuttlefish (Shinzato et al, 2018).The ability to perceive the tube as an obstacle to successful prey capture could explain why cuttlefish stop striking, but otherwise remain attentive towards prey, and quickly capture free prey after the procedure. More work is necessary to understand the multisensory inputs related to IP learning, as well the dynamics of the predatory response phases during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Automated tracking systems are valuable for studying predatory behavior in cuttlefish, because the behavior can be divided into three observable phases, which involves orientation and movement of the cuttlefish. The three phases of cuttlefish predatory behavior are attention, positioning, and, finally, the strike (Shinzato et al, 2018;Wells, 1958). The attention phase is visually prompted and begins when the cuttlefish orients its body towards the prey (Shinzato et al, 2018;Wells, 1958).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation